Genetically engineered bananas resistant to Xanthomonas wilt disease and nematodes - Tripathi, L.; Atkinson, H.; Roderick, H.; Kubiriba, Jerome; Tripathi, J.N. (Wiley, 2017)
Banana is an important staple food crop feeding more than 100 million Africans, but is subject to severe productivity constraints due to a range of pests and diseases. Banana Xanthomonas wilt caused by Xanthomonas campestris pv. musacearum is capable of entirely destroying a plantation while nematodes can cause losses up to 50% and increase susceptibility to other pests and diseases. Development of improved varieties of banana is fundamental in order to tackle these challenges. However, the sterile nature of the crop and the lack of resistance in Musa germplasm make improvement by traditional breeding techniques either impossible or extremely slow. Recent developments using genetic engineering have begun to address these problems. Transgenic banana expressing sweet pepper Hrap and Pflp genes have demonstrated complete resistance against X. campestris pv. musacearum in the field. Transgenic plantains expressing a cysteine proteinase inhibitors and/or synthetic peptide showed enhanced resistance to a mixed species population of nematodes in the field. Here, we review the genetic engineering technologies which have potential to improve agriculture and food security in Africa.